A critical analysis of Bent-Rib Metaphor ḥadīth: embracing women's uniqueness and empowerment - Zainan Nazri, Nurul Jannah; Zainan Nazri, Nurul Mukminah; Nazri, Mohd Arif (IIUM PRESS, 2023)
The Bent-Rib Metaphor ḥadīth has long been a subject of interpretation and debate. This critical analysis explores the multifaceted dimensions of this ḥadīth, shedding light on its linguistic nuances and the broader implications for women's uniqueness and empowerment within the framework of Islam. The ḥadīth, which likens women to a bent rib, is often cited to justify traditional gender roles and hierarchies within Muslim societies. However, this study delves into the historical context, and original Arabic text, dissecting the intricacies of the metaphor and its intended message. It highlights the importance of contextual analysis in interpreting religious texts, challenging the simplistic readings that have often perpetuated patriarchal interpretations. Furthermore, this analysis emphasizes the need to recognize and celebrate the uniqueness of women within Islamic teachings. It argues that the Bent-Rib Metaphor ḥadīthcan be interpreted as a symbol of diversity, complexity, and complementarity between genders, rather than justifying women's subordination. By promoting a more nuanced understanding of the ḥadīth, this study advocates for a broader role for women in religious, social, economic, and political spheres. The empowerment of women in Islamic societies is a central theme of this analysis, emphasizing that embracing the diversity and potential of women can lead to a more equitable and just society by Islamic principles. In conclusion, this critical examination of the Bent-Rib Metaphor ḥadīthoffers a fresh perspective on women's roles and rights within Islam and serves as a foundation for fostering a more inclusive interpretation of Islamic teachings.